Impacts of burial by sediment on decomposition and heavy metal concentrations of Suaeda salsa in intertidal zone of the Yellow River estuary, China. Issue 1 (15th March 2017) - Sun, Zhigao; Mou, Xiaojie; Zhang, Dangyu; Sun, Wanlong; Hu, Xingyun; Tian, Liping
Abstract: Three one-off burial treatments were designed in intertidal zone of the Yellow River estuary to determine the effects of sediment burial on decomposition and heavy metal levels of Suaeda salsa . Sediment burial showed significant effect on decomposition rate of S. salsa . With increasing burial depth, Cu, Zn, Cd and Co levels generally increased, while Cr and Mn levels decreased. Except for Zn, Mn, Cd and Co, stocks of Pb, Cr, Cu, Ni and V in S. salsa among burials were greatly different. The S. salsa in three burials was particular efficient in binding V and Co and releasing Pb, Zn and Cd, and, with increasing burial depth, stocks of Cr, Cu, Ni and Mn shifted from accumulation to release. In future, the eco-toxic risk of Pb, Cr, Cu, Zn, Ni, Mn and Cd exposure might be serious as the strong burial episodes occurred in S. salsa marsh. Highlights: Sediment burials showed significant influence on the decomposition rate of S. salsa . Cu, Zn, Cd and Co levels increased while Cr and Mn levels decreased with increasing burials. S. salsa was particular efficient in binding V and Co and releasing Pb, Zn and Cd. Cr, Cu, Ni and Mn in S. salsa shifted from accumulation to release with increasing burial depth. Potential eco-toxic risk of Pb, Cr, Cu, Zn, Ni, Mn and Cd exposure might be very serious.